2015
DOI: 10.1016/j.iswcr.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rye grass coverage on soil loss from loess slopes

Abstract: Vegetative coverage is commonly used to reduce urban slope soil erosion. Laboratory experimental study on soil erosion under grass covered slopes is conventionally time and space consuming. In this study, a new method is suggested to study the influences of vegetation coverage on soil erosion from a sloped loess surface under three slope gradients of 51, 151, and 251; four rye grass coverages of 0%, 25%, 50%, and 75%; and three rainfall intensities of 60, 90, and 120 mm/h with a silt-loamy loess soil. Rye gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Annual ryegrass also scored high for potential erosion control as it provided a high level of vegetative ground cover throughout the growing season and regenerated vegetative growth postharvest prior to winter. Previous studies have also shown that the use of ryegrass as a cover crop can substantially reduce soil erosion and sediment loss over various slope and rain intensities [113]. While the radish crops and annual ryegrass were not the greatest biomass producing crops, we did find that crop biomass production was also positively related to erosion control and weed suppression, likely due to biomass production, weed suppression and erosion control being all associated with greater leaf area, maximum canopy height and a more rapid spring growth rate.…”
Section: Soil Building and Erosion Controlmentioning
confidence: 99%
“…Annual ryegrass also scored high for potential erosion control as it provided a high level of vegetative ground cover throughout the growing season and regenerated vegetative growth postharvest prior to winter. Previous studies have also shown that the use of ryegrass as a cover crop can substantially reduce soil erosion and sediment loss over various slope and rain intensities [113]. While the radish crops and annual ryegrass were not the greatest biomass producing crops, we did find that crop biomass production was also positively related to erosion control and weed suppression, likely due to biomass production, weed suppression and erosion control being all associated with greater leaf area, maximum canopy height and a more rapid spring growth rate.…”
Section: Soil Building and Erosion Controlmentioning
confidence: 99%
“…Its temporal and spatial patterns reflect carbon sink potential of grassland vegetation [7], [8]. In addition, grassland AGB and its change directly reflect degree of grassland degradation, soil erosion [9]- [11] and desertification [12]. In practice, changes in grassland AGB can be used to monitor pasture overgrazing and land use change [13].…”
Section: Introductionmentioning
confidence: 99%
“…Important cover-related parameters and functions include aboveground biomass [2][3][4][5], evapotranspiration [6] and leaf area index [7]. In addition, plant coverage and its changes over time have been directly used as indicators of grassland degradation, soil erosion [8][9][10] and desertification [11]. Under actual production conditions, changes in grassland cover can reveal over-grazing, aid in the monitoring of land use (e.g., changes between grassland and farmland) [12], and provide an early warning of grassland degradation.…”
Section: Introductionmentioning
confidence: 99%